Alloy Nanoparticle Fabrication by Mechanical Approach. (2019) - Showman, Samuel; Bhagwat, Anish; Sanders, James; Page, Kimberly; Hampikian, Helen; Li, Chunfei
Abstract: This paper reports the results of preparing alloy nanoparticles by mechanical grinding followed by filtration to sort the particles according to size. Although the long-term goal of this work is to prepare icosahedral quasicrystalline nanoparticles, the alloy used in this study is of Al65 Cu25 Fe15 composition and multi phases, under the assumption that the established procedure is applicable to future quasicrystalline nanoparticle fabrication. The obtained particle size and elemental information were investigated using scanning electron microscopy and energy dispersive x-ray spectroscopy. Problems with filter fragment fall-out and salt contamination were encountered and procedures to address the problems have been suggested and tested. The study is successful in obtaining alloy particles with reduced sizes.